Efficacy and Safety of Botulinum Toxin vs. Placebo in Depression: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Qian, Huan; Shao, Fangjie; Lenahan, Cameron; Shao, Anwen; Li, Yingjun (Frontiers in Psychiatry, 2020)
Background Major depressive disorder (MDD) is a serious mental disorder that represents a substantial public health problem. Several trials have been undertaken to investigate the role of Botulinum toxin type A (BTX-A) in the treatment of MDD, but the conclusions were controversial. To examine the efficacy and safety of BTX-A versus placebo on patients with a clinical diagnosis of MDD, we conducted this systematic review and meta-analysis. Methods A systematic search was conducted for all relevant randomized controlled trials (RCTs) in PubMed and Web of Science from inception to 17 June 2020. All published studies that investigated the efficacy and safety of BTX-A injections on patients with a clinical diagnosis of MDD were included. The overall effect size was summarized using a random-effects meta-analysis model. The primary outcomes of the present meta-analysis were the changes in depressive rating scale at week 6 after BTX-A injection compared with placebo. Furthermore, the safety of BTX-A injections was assessed. Results Five RCTs with a total of 417 participants (189 patients in the BTX-A group, 228 patients in placebo group) were eligible in this meta-analysis. The results indicated an overall positive effect of BTX-A injections on reducing the depressive symptoms of patients with MDD (Hedge’s g, -0.82; 95% CI, -1.38 to -0.27) with large effect size. Differences are likely explained by the dose of BTX-As and the gender of the participants. Our findings also highlighted that BTX-A injections were generally well-tolerated, with only mild and temporary adverse events reported. Conclusions The present meta-analysis provides evidence that BTX-A injections are associated with a statistically significant improvement in depressive symptoms. BTX-A injections are generally safe, and may provide a new, alternative option for the treatment of depression.